2023
DOI: 10.1002/jmv.28700
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment and validation of a plaque reduction neutralization test (PRNT) in support to yellow fever diagnostic and vaccine clinical trials

Abstract: Yellow fever (YF) virus is a mosquito-borne virus belonging to the Flaviviridae family that circulates in tropical and subtropical areas of Africa and South America. Despite the availability of an effective vaccine, YF remains a threat to travelers, residents of endemic areas, and unvaccinated populations. YF vaccination and natural infection both induce the production of neutralizing antibodies. Serological diagnostic methods detecting YF virus-specific antibodies demonstrate high levels of cross-reactivities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…No positive correlation was detected for the other three viral serotypes DENV2 ( r = 0.36, p = 0.29), DENV3 ( r = −0.42, p = 0.41) and DENV4 ( r = −0.17, p = 0.62). A similar analysis but using PRNT90, which is considered of higher specificity than PRNT50 in the serodiagnostic of Flaviviruses, 26 Spearman coefficients for the correlation analysis between serotype‐dependent neutralization capacity and anti‐DIII titers are statistically significant for sera from early convalescence (File : Figure ). However, for the sera from late convalescence there is a significant decreased in the correlation of these two determinations, and Spearman correlation coefficients are not statistically significant (File : Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No positive correlation was detected for the other three viral serotypes DENV2 ( r = 0.36, p = 0.29), DENV3 ( r = −0.42, p = 0.41) and DENV4 ( r = −0.17, p = 0.62). A similar analysis but using PRNT90, which is considered of higher specificity than PRNT50 in the serodiagnostic of Flaviviruses, 26 Spearman coefficients for the correlation analysis between serotype‐dependent neutralization capacity and anti‐DIII titers are statistically significant for sera from early convalescence (File : Figure ). However, for the sera from late convalescence there is a significant decreased in the correlation of these two determinations, and Spearman correlation coefficients are not statistically significant (File : Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The 24 sera were tittered by ELISA to determine the neutralizing capacity of each serum to compare it with the anti-DIII IgG titer (File S1: Figure S2; Table S2). A similar analysis but using PRNT90, which is considered of higher specificity than PRNT50 in the serodiagnostic of Flaviviruses, 26 Spearman coefficients for the correlation analysis between serotype-dependent neutralization capacity and anti-DIII titers are statistically significant for sera from early convalescence (File S1:…”
Section: Calculations and Statistics Proceduresmentioning
confidence: 99%
“…A recent study assessed the intra- and inter-assay precisions, dilutability, specificity, and lower limit of quantification (LLOQ) using international standard YF serum and sera from vaccinees and human specimens collected through YF surveillance. The results showed that the PRNT assay showed 100% of intra-assay precision, 95.6% of inter-assay precision, 100% of specificity, 100% of LLOQ, and 95.3% of dilutability [ 52 ]. The main limitation in PRNT is that it cannot differentiate the isotype of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Assay validity criteria included (i) the absence of PFU in the cell control well; (ii) neutralization by positive control sera, and no neutralization by negative control sera; (iii) the observed number of PFU for each triplicate (per each dilution of each mock or infected sample tested) in an experiment were within a 3-fold difference of the median PFU count (Dia et al, 2023; Timiryasova et al, 2013) and; (iv) the observation of 70 to 180 PFU in virus control wells. The median percentage of viral neutralization was estimated for each experiment comparing the median number of PFUs in virus wells to those in wells where the virus was incubated with liver homogenates, positive and negative controls.…”
Section: Methodsmentioning
confidence: 99%